2018
DOI: 10.3390/rs10060950
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Wheat Phenotyping Traits Using Ground and Aerial Imagery

Abstract: Abstract:This study evaluates an aerial and ground imaging platform for assessment of canopy development in a wheat field. The dependence of two canopy traits, height and vigour, on fertilizer treatment was observed in a field trial comprised of ten varieties of spring wheat. A custom-built mobile ground platform (MGP) and an unmanned aerial vehicle (UAV) were deployed at the experimental site for standard red, green and blue (RGB) image collection on five occasions. Meanwhile, reference field measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
1
27
2
Order By: Relevance
“…For ground platform, ground fixed scanning system [15,22,30,35], handheld-based field measuring [11,14,16,32], mobile ground platform (MGP) [14,20], and lifting hoist-based elevated platform [12,36] were reported for different crops types ( Figure 2). These platforms were easy-to-use with low cost, but data acquisition was semi-automatic.…”
Section: Platforms and Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For ground platform, ground fixed scanning system [15,22,30,35], handheld-based field measuring [11,14,16,32], mobile ground platform (MGP) [14,20], and lifting hoist-based elevated platform [12,36] were reported for different crops types ( Figure 2). These platforms were easy-to-use with low cost, but data acquisition was semi-automatic.…”
Section: Platforms and Sensorsmentioning
confidence: 99%
“…This is clearly far more efficient compared to traditional manual measurement. Khan et al [20] also compared the estimating accuracy based on mobile ground platform (MGP) and UAV platform, and showed that the estimated canopy height derived from MGP imagery were better than UAV imagery, while the opposite results were obtained regarding the estimating of canopy vigor.…”
Section: Platforms and Sensorsmentioning
confidence: 99%
“…Plant height is a crucial variable connected to stability, yield potential and lodging resistance. This variable has been assessed by UAS as a Structure from Motion (SfM), obtaining high correlations with ground reference measurements for barley (Bendig et al, 2014), wheat (Khan et al,2018), poppy (Iqbal et al, 2017) and sorghum (Hu et al, 2018). In this research, senseFly eBee was chosen as a UAS, providing great flexibility and speed to accomplish mapping at high spatial and temporal resolution using an onboard Canon G9X compact digital camera, working in the visible spectrum (Red-Green-Blue).The images are processed through a fully automatic photogrammetric pipeline by the computation of the view of each image and, subsequently, the generation of a dense and scaled 3D model of the crop.…”
Section: Introductionmentioning
confidence: 99%
“…After publication of the research paper [1], the Remote Sensing editorial office noticed errors and wish to make the following corrections. In Equation 1, "vigourmGRVI" should be changed to "vigour~GRVI".…”
mentioning
confidence: 99%
“…The changes do not affect the scientific results. The original manuscript [1] will be updated and will remain online on the article webpage, with a reference to this Erratum.…”
mentioning
confidence: 99%